14q deletions are associated with trisomy 12, NOTCH1 mutations and unmutated IGHV genes in chronic lymphocytic leukemia and small lymphocytic lymphoma. Issue 8 (12th April 2014) - Cosson, Adrien; Chapiro, Elise; Belhouachi, Nabila; Cung, Hong‐Anh; Keren, Boris; Damm, Frederik; Algrin, Caroline; Lefebvre, Christine; Fert‐Ferrer, Sandra; Luquet, Isabelle; Gachard, Nathalie; Mugneret, Francine; et al.
<x xml:space="preserve">Abstract</x> Deletions of the long arm of chromosome 14 [del(14q)] are rare but recurrently observed in mature B‐cell neoplasms, particularly in chronic lymphocytic leukemia (CLL). To further characterize this aberration, we studied 81 cases with del(14q): 54 of CLL and 27 of small lymphocytic lymphoma (SLL), the largest reported series to date. Using karyotype and fluorescence in situ hybridization (FISH), the most frequent additional abnormality was trisomy 12 (tri12), observed in 28/79 (35%) cases, followed by del13q14 (12/79, 15%), delTP53 (11/80, 14%) delATM (5/79, 6%), and del6q21 (3/76, 4%). IGHV genes were unmutated in 41/53 (77%) patients, with a high frequency of IGHV1‐69 (21/52, 40%). NOTCH1 gene was mutated in 14/45 (31%) patients. There was no significant difference in cytogenetic and molecular abnormalities between CLL and SLL. Investigations using FISH and SNP‐array demonstrated the heterogeneous size of the 14q deletions. However, a group with the same del(14)(q24.1q32.33) was identified in 48% of cases. In this group, tri12 (P = 0.004) and NOTCH1 mutations (P = 0.02) were significantly more frequent than in the other patients. In CLL patients with del(14q), median treatment‐free survival (TFS) was 27 months. In conclusion, del(14q) is associated with tri12 and with pejorative prognostic factors: unmutated IGHV genes (with over‐representation of the IGHV1‐69 repertoire), NOTCH1 mutations, and a short TFS. © 2014 Wiley Periodicals, Inc.